The microbial electrochemical Peltier heat: an energetic burden and engineering chance for primary microbial electrochemical technologies. Issue 8 (1st July 2016) - Korth, Benjamin; Maskow, Thomas; Picioreanu, Cristian; Harnisch, Falk
Abstract : Microbes shoveling electrons heat up: combining calorimetry with microbial electrochemistry allows deciphering heat fluxes of electroactive microorganisms. Abstract : Bioelectrocalorimetry allows assessing the heat (enthalpy) balance and revealing the microbial electrochemical Peltier heat of biofilm electrodes. This effect accounts for a heat formation of 27 ± 6 kJ mol −1 of electrons transferred and represents a significant energy loss for primary microbial electrochemical technologies.